Comparison of flavour qualities of three sourced Eriocheir sinensis. (1st June 2016) - Wang, Shuai; He, Yu; Wang, Yayue; Tao, Ningping; Wu, Xugan; Wang, Xichang; Qiu, Weiqiang; Ma, Mingjun
Highlights: The taste/aroma profiles of three types of Chinese mitten crabs were examined. Equivalent umami concentrations ( EUC ) of three edible parts of Chinese mitten crabs were confirmed. High contents of nucleotides in ovaries produced the strong umami taste of female crabs. The key aroma compounds of the three crabs were determined. The umami intensities of the three crabs correlated with their perceived market values. Abstract: Flavour qualities of three edible parts of three types of Chinese mitten crab from different areas were examined. The flavour profiles detected by E-tongue and E-nose showed that differences existed in tastes and odours among wild-caught crabs (WC), Yangcheng crabs (YC) and Chongming crabs (CM). The total free amino acids contents of WC were all at the highest level in meat, gonads and hepatopancreas. Ovaries had the highest nucleotides content and equivalent umami concentration ( EUC ) than other tissues in both female and male. The EUC was the highest in all parts of WC, followed by YC and CM. The total content of nine key volatile compounds was the highest for WC in the gonads and hepatopancreas; in the muscle, they were the highest in female YC and male CM, but the lowest for WC.